A new tiger beetle from the Trans-Mexican Volcanic Belt (Coleoptera, Cicindelidae, Cicindelini) - Duran, Daniel P.; Roman, Stephen J. (Zootaxa, 2020)
A new tiger beetle species, Cicindelidia cyanipleura Duran and Roman n. sp., of the tribe Cicindelini, is described from the southwestern section of the Trans-Mexican Volcanic Belt. Superficially, it appears to be most closely related to C. rufiventris (Dejean, 1825) but is distinguished on the basis of multiple morphological characters and behavior. Given the rock-loving natural history of the species, escape behavior, polished pronotum, and small body size, it may be more closely related to the petrophiles C. laetipennis (Horn, 1913) or C. politula (LeConte, 1875), from which it is distinguished on the basis of multiple morphological characters and biogeography.